Eco-friendly green synthesis: catalytic activity of nickel hydroxide nanoparticles. (20th February 2019) - Nagajyothi, P C; Deyarayapalli, K C; Tettey, C O; Vattikuti, S V Prabhakar; Shim, Jaesool
Abstract: Nowadays many textile industries release their waste products directly into water resources like lakes, rivers and ground water has become a serious problem. These dye pollutants are difficult to remove by conventional methods like adsorption, filtration, coagulation etc. Hence, there is a need to develop more appropriate and inexpensive methods of industrial effluent treatment. In this work, we report a green route for the synthesis of nickel hydroxide nanoparticles (Ni(OH)2 NPs) using an aqueous fruit extract of star anise ( Illiciumverum ) under optimized hydrothermal conditions. The morphology, crystalline structure, chemical composition, and catalytic activity of the synthesized Ni(OH)2 NPs were evaluated using FTIR, XRD, XPS, HR-TEM, SAED and SEM-EDX. The XRD results and HR-TEM images revealed that the Ni(OH)2 NPs have mixed morphologies including spherical, hexagonal, and rod shapes with average particle size of ∼16.1 nm and consist of the β –phase. The obtained Ni(OH)2 NPs were proven to be efficient catalyst which improved the reduction rates of the rhodamine B and rhodamine 6G (RhB and Rh6G) dyes.